Corrective Feedback to Improve Students Writing Ability - LINA MARIANA; Diani Nurhajati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2017)
This article refers to a Lesson Study research implementing Corrective Feedback to enhance the students writing ability. The research aims to identify: (1) kinds and types of corrective feedback given by the lecturer to improve the students writing ability and (2) the process of giving corrective feedback in Creative Writing classroom. It was conducted to 37 second year students in the odd semester of 2016/2017 academic year of a University of Nusantara PGRI in Kediri, East Java. Questionaire, interview and tests were given before and after the implementation of corrective feedback activities and it had two cycles, consisting of three main stages, they are Plan, Do and See stage. The instruments used were questionnaire and interviews were given to the students before and after the implementation. The result showed that corrective feedback activities improved students writing ability. The students were interested in creative writing class as they paid good attention and felt fun when they were involved in making creative paragraphs consisting of a short story to be presented in front of the class and expressed their ideas upon the stories given. Their worries of making mistakes were decreased since the lecturer gave oral corrective feedback directly when they made mistakes in deciding the intrinsic elements of making short story and also when the lecturer made some notes upon their works as written corrective feedback discussing about the aspects of writing such as grammatical structure of sentences, vocabulary, ideas, organization and also mechanic. After having some beneficial notes to be revised the students will absolutely get the points about what the mistakes and weaknesses they made that not to be done again for the next project.